2019
DOI: 10.1029/2018wr024489
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation Suppression From Water Bodies Using Floating Covers: Laboratory Studies of Cover Type, Wind, and Radiation Effects

Abstract: Water reservoirs have been used to mitigate seasonal water shortages since the dawn of civilization. Present day use of water reservoirs continues to expand to meet the increasing demand for irrigation water and to mitigate effects of climate change and droughts. Losses to evaporation are an important challenge to water storage efficiency in arid regions. We study the use and efficiency of self-assembling floating covers as a simple and scalable solution to evaporation suppression. We report laboratory-scale s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 19 publications
(54 reference statements)
6
35
0
Order By: Relevance
“…As reported in other studies (Lehmann et al, 2019), despite the very high surface temperatures of the black covers compared to the white covers (up to 30°C difference, see Figure 3), the overall evaporation suppression performance of the different color covers was similar. Nevertheless, the high black cover temperatures affected the water temperatures in the reservoirs top layer as evidenced by considerably higher temperatures under black relative to white disks (see Figure S3).…”
Section: Evaporation Suppressionsupporting
confidence: 84%
See 1 more Smart Citation
“…As reported in other studies (Lehmann et al, 2019), despite the very high surface temperatures of the black covers compared to the white covers (up to 30°C difference, see Figure 3), the overall evaporation suppression performance of the different color covers was similar. Nevertheless, the high black cover temperatures affected the water temperatures in the reservoirs top layer as evidenced by considerably higher temperatures under black relative to white disks (see Figure S3).…”
Section: Evaporation Suppressionsupporting
confidence: 84%
“…Other studies have shown that suppression efficiency of floating covers varies with cover properties (cover fraction, geometries, and material properties) and atmospheric forcing of evaporation process (Assouline et al, 2011). Based on lab experiments in a shallow water basin using floating spheres (0.04 m in diameter), Lehmann et al (2019) have found that evaporation suppression was about 70% irrespective of boundary forcing (wind and radiation). Despite the higher temperature of black covers, no difference in evaporation suppression was measured by Lehmann et al (2019) compared to white spheres and disks.…”
mentioning
confidence: 99%
“…Cheap floating cover elements could be a simple and scalable solution for suppressing evaporative losses from the many small reservoirs that serve largely rural populations in semi-arid regions. Results from recent studies have shown that across a wide range of climatic conditions, such covers suppress between 70 and 85% of the evaporation relative to uncovered water surfaces [33,46]. Floating covers reduce the exposed water surface, increase the effective boundary layer over the surface, and shift radiation and heat exchange from the water surface to the top surfaces of the covers [33,46].…”
Section: Evaporation Suppression Using Floating Covers-water Saving Pmentioning
confidence: 99%
“…Results from recent studies have shown that across a wide range of climatic conditions, such covers suppress between 70 and 85% of the evaporation relative to uncovered water surfaces [33,46]. Floating covers reduce the exposed water surface, increase the effective boundary layer over the surface, and shift radiation and heat exchange from the water surface to the top surfaces of the covers [33,46]. The packing of floating spheres or discs permit light penetration and gas exchange through the 9% uncovered area (gaps formed between the elements), thus permitting ecological functions (we report preliminary results from an ongoing field experiment in SI-section 3 and figure S8).…”
Section: Evaporation Suppression Using Floating Covers-water Saving Pmentioning
confidence: 99%
See 1 more Smart Citation